Job performance of lecturers in a centre of foundation studies / Nurhamizah Ishak and Leele Susana Jamian - Ishak, Nurhamizah; Jamian, Leele Susana (UiTM Cawangan Johor, 2019)
This study looks at the levels of job performance among the lecturers in a centre of foundation studies owned by a public university in Selangor. Questionnaires that consist of close-ended items and openended items were used to collect data on the sample. Due to its quite small population size, total population sampling method is applied. Out of 140 lecturers, only 86 completed the questionnaires. The findings revealed that the sample have high overall job performance level. They also scored high job performance level in the two main dimensions that were measured such as task performance and contextual performance. Besides, there was a significant difference between job performance and departments of the sample. As for the implications of this study, it contributes to the corpus of knowledge in the area of job performance in local context and provides empirical data to assist Ministry of Higher Education in conducting strategic planning to enhance job performance amongst lecturers in institutions of higher educations (IHE).